Evaluation of hair growth potential of Angustifolia leaves hair gel in rats - Bharti, Manu; Bhardwaj, Anjali; Parveen, Neha; Gupta, Ashwani (Indian Journal of Pharmacy & Drug Studies, 2025)
Background: Hair loss, or alopecia, significantly affects both physical appearance and psychological well-being, particularly in cases such as androgenetic alopecia and alopecia areata. Current pharmacological treatments like minoxidil and finasteride have limitations, including side effects and decreased long-term efficacy. Objectives: An ethanolic extract of Senna angustifolia (EESA), a traditionally used Ayurvedic plant, was evaluated for its hair growth-promoting potential using in vivo rat models. Methodology: The research began with the successful extraction of phytoconstituents from Senna angustifolia leaves using Soxhlet extraction. The gel was formulated into two concentrations—2.5% and 5% EESA—and compared with a control and standard 2% minoxidil treatment. Hair growth studies were performed on Wistar rats by evaluating both qualitative (initiation and completion of hair growth) and quantitative parameters (hair length, follicle count, and histological observations). Results: Qualitative hair growth analysis indicated that both EESA concentrations accelerated hair growth, with 5% EESA (HG2) showing a significantly faster initiation and completion time (7.01 and 32.4 days, respectively) compared to control (13.8 and 42.6 days) and even slightly outperforming minoxidil (7.07 and 33.0 days). Quantitative analysis supported these findings. By day 30, HG2 achieved the greatest hair length (2.8 mm), marginally higher than minoxidil (2.4 mm) and significantly more than the control (1.2 mm). Histopathological studies corroborated these findings with increased follicle density and size. Conclusion: These results suggest that Senna angustifolia extract exhibits promising hair growth-stimulatory effects and may serve as a natural alternative or complementary treatment for alopecia with minimal irritation potential. Further clinical investigations are warranted to explore its therapeutic application in humans.